"Missing" acute coronary syndrome hospitalizations during the COVID‐19 era in Greece: Medical care avoidance combined with a true reduction in incidence?. Issue 10 (21st July 2020) - Papafaklis, Michail I.; Katsouras, Christos S.; Tsigkas, Grigorios; Toutouzas, Konstantinos; Davlouros, Periklis; Hahalis, George N.; Kousta, Maria S.; Styliadis, Ioannis G.; Triantafyllou, Konstantinos; Pappas, Loukas; Tsiourantani, Fotini; Varytimiadi, Efthymia; et al.
Abstract: Background: Reports from countries severely hit by the COVID‐19 pandemic suggest a decline in acute coronary syndrome (ACS)‐related hospitalizations. The generalizability of this observation on ACS admissions and possible related causes in countries with low COVID‐19 incidence are not known. Hypothesis: ACS admissions were reduced in a country spared by COVID‐19. Methods: We conducted a nationwide study on the incidence rates of ACS‐related admissions during a 6‐week period of the COVID‐19 outbreak and the corresponding control period in 2019 in Greece, a country with strict social measures, low COVID‐19 incidence, and no excess in mortality. Results: ACS admissions in the COVID‐19 (n = 771) compared with the control (n = 1077) period were reduced overall (incidence rate ratio [IRR]: 0.72, P < .001) and for each ACS type (ST‐segment elevation myocardial infarction [STEMI]: IRR: 0.76, P = .001; non‐STEMI: IRR: 0.74, P < .001; and unstable angina [UA]: IRR: 0.63, P = .002). The decrease in STEMI admissions was stable throughout the COVID‐19 period (temporal correlation; R 2 = 0.11, P = .53), whereas there was a gradual decline in non‐STEMI/UA admissions (R 2 = 0.75, P = .026) following the progressively stricter social measures. During the COVID‐19 period, patients admitted with ACS presented more frequently with left ventricular systolic impairment (22.2 vs 15.5% control period; P < .001). Conclusions: We observed a reduction in ACS hospitalizations during the COVID‐19 outbreak in a country with strict social measures, low community transmission, and no excess in mortality. Medical care avoidance behavior is an important factor for these observations, while a true reduction of the ACS incidence due to self‐isolation/quarantining may have also played a role.